The nature of mathematics - Smith, Karl J. (Thomson, 2004)
Karl Smith's loyal customers adopt his book for its clear writing, its coverage of historical topics, selection of topics, level, exercise sets (featuring great applications problems), and emphasis on problem solving. Since the First Edition of Smith's text was published, thousands of liberal arts students have "experienced" mathematics rather than just doing problems. Smith's writing style gives students the confidence and ability to function mathematically in their everyday lives. The emphasis on problem solving and estimation, along with numerous in-text study aids, encourages students to understand the concepts while mastering techniques.